Analisis Penyelesaian Perkara Perceraian Umat Hindu di Pengadilan Negeri Denpasar - Budiawan, Ketut (Belom Bahadat, 2024)
This study describes how the settlement of Hindu marriage cases through the court because until now the Hindu community in the Implementation of the Legal System does not yet have a Hindu Law Compilation as a Legal Substance in the process of marital settlement. The approach used is a qualitative approach with a case study research design in the Denpasar District Court. Legally substance, the source of applicable law is the source of civil procedural law as well as the principles and provisions that apply in general justice, Customary Law, Jurisprudence, expert opinion. Legal sources related to the teachings of Hinduism based on the results of interviews with judges, the judge said that had never been in the interpretation of the case decided sourced from Hindu Law Sources because the legal sumer in question does not yet exist. Furthermore, the results of the study indicate that the tendency of civil sub-classification divorce case data within a period of 2 months and 27 days has increased in the jurisdiction of the Denpasar District Court of the City of Denpasar and Badung Regency consisting of 10 Districts and 105 villages / sub-districts having divorce cases with the number of cases as many as 201 cases, which already have permanent legal decisions as many as 74 cases and those that are still in a trial are 127 cases. Legal culture as the attitude or appreciation of the community towards the law and the legal system is very high, proven based on case data that is resolved through the courts, meaning that trust in the law, values, ideas or hopes, and expectations become an important part of the community Hinduism in Denpasar City and Badung Regency which are the jurisdiction of the Denpasar District Court to obtain the values ​​of justice. The forms of settlement of marital cases in court and the implications for the position of Hindu women in the legal system through mediation are regulated in the Supreme Court Regulation of the Republic of Indonesia Number 1 of 2016 and the trial process until the final legal verdict. Keywords: Marriage Matters, Religious Norms, Legal Norms, Legal System, Hindu Women.